Analysis of Public Policies in Indonesia’s Palm Oil Industry to Support Sustainable Development - Taufiq Hidayat; Suryadi Fajri (ARISTO, 2026)
Indonesia's palm oil industry is facing a sustainability crisis driven by large-scale deforestation, ecosystem degradation, high carbon emissions, and human rights violations. These issues are exacerbated by weak land governance, productivity disparities, and the lack of a holistic integration of public policies in responding to global ecological, social, and economic pressures. This study aims to analyze palm oil policies within the framework of sustainable development using the Multiple Streams Framework. The research employs a qualitative method through a literature review, critically examining government policies and related reports on palm oil governance in the context of sustainable development. Findings reveal that the industry's sustainability is hindered by the misalignment between economic growth, environmental conservation, and social justice. Although the government has introduced policies such as B40 biodiesel and the National Action Plan for Sustainable Palm Oil (RAN-KSB), major challenges persist, particularly in weak governance, social inequality, and environmental damage. This study recommends the reformulation of more transparent and sustainable policies to promote a more responsible palm oil industry. Keywords: Palm Oil;  Sustainable Development; Public Policy;